The atomic scale mechanisms of the interaction between pore and grain boundary during sintering. (August 2022) - Tang, Sai; Zhang, Zhichen; Cai, Qingshan; Ma, Yunzhu; Liu, Wensheng
Abstract: The grain boundary (GB)-pore interaction is crucial to grain evolution and densification in materials sintering. In this work, by using the phase-field crystal model, we performed atomic scale simulations to investigate the microscopic mechanisms for the GB-pore interaction. The influence of pore on grain growth is clarified. The results indicate that a singular pore retards grain growth mainly through inhibiting grain rotation. Two modes, the pinning and bypassing mode, of GB-pore interaction are observed. In the pinning mode, the moving circular GB of a shrinking grain is pinned by the two junctions connecting the GB and the pore surface in the case of high GB misorientation, or by absorbing intergranular dislocations in the case of small GB misorientation. High misorientation GBs interact with a pore through the two junctions directly, while small misorientation GBs through the long range elastic field of the intergranular dislocations. The bypassing mode particularly occurs in the case of a very low angle tilt GB and a nano-pore. The GB quickly bypasses the pore locating between two neighboring intergranular dislocations through local lattice distortion. Graphical Abstract: ga1